Geberverhalten in der internationalen Entwicklungspolitik: Schwierigkeiten beim Umgang mit dem Spannungsfeld Rechenschaftspflichten - Simon Hartmann (Austrian Foundation for Development Research (ÖFSE), 2011)
Partnerschaft zwischen Geber- und Empfängerländern soll zu mehr entwicklungspolitischer Wirksamkeit beitragen. Die Stärkung der Eigenverantwortung der Empfänger ist dabei ein zentrales Prinzip. Dazu bekannten sich zumindest die traditionellen DAC-Geber nicht zuletzt in der "Erklärung von Paris über die Wirksamkeit der Entwicklungszusammenarbeit" von 2005. [...] Ziel des vorliegenden Papers ist es, anhand der Diskussion entwicklungspolitischer Partnerschaften im Spannungsfeld Eigenverantwortung und Rechenschaftspflichten, zu einem besseren Verständnis der aktuell wichtigsten entwicklungspolitischen Herausforderungen in diesem Zusammenhang beizutragen. Die Schlussfolgerungen am Ende des Papers liefern diesbezüglich eine Orientierung für die Gestaltung von Entwicklungspolitik. – – The current OECD aid paradigm suggests that partnership produces more aid effectiveness. Donors widely agree on partner country ownership of development policy as key principle for more effective aid, as stated in the Paris Declaration on Aid Effectiveness. However this says little about donor behavior in the ever-day political business. Two-way effective domestic accountability mechanisms in developing countries are key for sustainable development. Anyway, donors are influencing distribution of power within developing countries by supporting actors from the state and/or the society. Hence it happens a lot that donors at least gradually undermine existing domestic accountability mechanisms. "Do no harm" to them is a first step to provide space for both, aid and development effectiveness. Secondly, donors have to think about ways to support the domestic accountability mechanisms in recipient countries. Adapting on existing domestic institutions has to be given priority. Choice in development policy has to be based on deep insights in local and regional context. Together with the international environment this is the most important factor which shapes the policy space for donor recipient negotiations and the bargaining power on both sides. Inseparable from these considerations, a more open debate on competing interests from various other policy fields is rather needed. This analysis aims at challenges of development partnerships by drawing on discrepancies between ownership and accountability mechanism in the every-day business of development policy. Raising and grinding awareness on problems connected with these challenges is the main purpose of this paper. The concluding remarks section finally shall provide orientation for approaching them.
Keywords: 330; Entwicklungshilfe; Wirkungsanalyse; Entwicklungshilfe; Nord-Süd-Beziehungen